Transforming the Panama Canal's Transport Pattern into a Tourist Attraction: An Analytical Study (The Peerian Journal, 2025)
Our research aims to transform the Panama Canal’s transportation model into a tourist attraction, to highlight the Panama Canal, and to analyze the possibility of transforming it into a global tourist destination by exploring the opportunities and challenges associated with this transformation, as well as highlighting its economic and geographical role and importance. The research will address the historical and engineering aspects of the canal, in addition to analyzing current patterns of maritime transport and their impact on tourism according to an analytical methodology based on historical and statistical data, in addition to international comparisons